Combining and competing effects between precipitation and temperature on Holocene fire regime evolution inferred from a sedimentary black carbon record in southwestern China. Issue 1 (January 2020) - Ning, Dongliang; Zhang, Enlou; Shulmeister, James; Chang, Jie; Sun, Weiwei; Ni, Zhenyu
Abstract: Wildfires are sensitive to climate change, but their response to changes in temperature and precipitation on long timescales is still disputed. In this study, we present a ~9.4 ka black carbon mass sedimentation rate (BCMSR) record from Lake Ximenglongtan (XMLT), southwestern China, to elucidate the Holocene fire regime and its linkages to climatic conditions. The results indicate that the regional fire activity was low during the early Holocene (before 7.6 cal ka BP), increased notably at 7.6 cal ka BP, and continued to increase gradually during the mid- to late Holocene until 2.2 ka. The episodes of higher fire occurrence reflected by higher BCMSR over the last 2.2 ka might be more likely related to the intensified human activities. The cool and humid climate during the early Holocene limited the spread of fire, while warming and drying at ~7.6 cal ka BP triggered higher fire occurrence. Instead of temperature, changes in precipitation dominated fire regime variation during the mid- to late Holocene. On millennial timescales, we suggest that Holocene fire variability has been predominantly controlled by the combined effects of Northern Hemisphere (NH) summer and winter insolation that influenced monsoonal precipitation and fire season temperature, respectively. Indian Ocean Dipole (IOD) events may also have affected fire incidence through influencing monsoon intensity.